Assessing local action groups and auctions as institutional alternatives for designing and implementing agri-environmental measures in the EU - results from an expert survey - Jor̈g Eggers; Evy Mettepenningen; Volker Beckmann (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2008)
The new European Council Regulation on support for rural development (EC) No. 1698/2005 has opened up the opportunity for two important innovations for the design and implementation of agri-environmental measures: local action groups (LAG) according to the LEADER approach and calls for tender. The article firstly reviews the political and scientific debate on the possible performance of these innovations and, secondly, analyses how agents in public administrations, private associations and research institutes assess them. This ex-ante evaluation is based on 279 interviews in nine EU member states, carried out in the context of an EU-research project in the Sixth Framework Programme in 2006. The results show that (1) the performance of LAG is generally rated higher than that of auctions, (2) different actors show similar evaluation patterns, thus forming advocacy coalitions, and (3) experiences and learning may play an important role in the actors' evaluation of both innovations. – – Die neue Ratsverordnung zur ländlichen Entwicklung (EG) Nr. 1698/2005 eröffnet zwei neue Möglichkeiten der Gestaltung und Implementierung von Agrarumweltmaßnahmen: lokale Aktionsgruppen (LAG) im Sinne des LEADER-Ansatzes und Ausschreibungen. Der Beitrag fasst zunächst die politische und wissenschaftliche Diskussion zur Leistungsfähigkeit dieser Innovationen zusammen, um im zweiten Schritt zu analysieren, wie relevante Akteure aus der öffentlichen Verwaltung, den privatwirtschaftlichen Verbänden und aus Forschungseinrichtungen diese bewerten. Diese Ex-ante-Bewertung basiert auf 279 Interviews in neun EU-Mitgliedsstaaten, die im Verlauf eines EU-Forschungsprojektes innerhalb des 6. Forschungsrahmenprogramms 2006 durchgeführt wurden. Die Ergebnisse zeigen, dass (1) die Leistungen von LAG grundsätzlich besser evaluiert werden als die von Ausschreibungen, (2) verschiedene Akteure ähnliche Muster der Evaluierung aufweisen und damit Befürwortungskoalitionen bilden, (3) Erfahrungen und Lernprozesse eine wichtige Rolle bei Evaluierung durch die Akteure spielen können (Quelle: Verlag)
Keywords: 330; EU-Agrarpolitik; Umweltpolitik; Institutioneller Wandel; Dezentralisierung; Ausschreibung; Umweltschutz; Bewertung; EU-Staaten